Large hadron collider phenomenology: proceedings of the Fifty Seventh Scottish Universities Summer School in Physics, St. Andrews, 17 August to 29 August 2003 - Soler, F . J . P . (Institute of Physics Pub., 2011)
With the Large Hadron Collider (LHC) under construction and due to come online in 2007, it is appropriate to engage in a focused review on LHC phenomenology. At a time when most of the experimental effort is centered on detector construction and software development, it is vitally important to direct the experimental community and, in particular, new researchers on the physics phenomena expected from the LHC. Large Hadron Collider Phenomenology covers the capabilities of LHC, from searches for the Higgs boson and physics beyond the standard model to detailed studies of quantum chromodynamics, the B-physics sectors, and the properties of hadronic matter at high energy density as realized in heavy-ion collisions.